Literature Review: Pengaruh Pemberian Kombinasi Makanan terhadap Anak Lahir Stunting sebagai Upaya untuk Menurunkan Kejadian Malnutrisi di Indonesia - Mega Anggraeni (Journal of Bionursing, 2021)
Introduction: Nutrition status is an indicator level of child welfare in Indonesia. One of the factors that affect nutritional status is food intake. Fulfilling the need for a balanced intake of food starts from the implantation until the child is 24 months old. In this age period is a period of growth that will determine the physical form of the child. Stunting is a chronic malnutrition disease that the body becomes short. The impact of stunted child birth is growth becomes inhibited, decreased cognitive function, and decreased immune function. Therefore, it is necessary to handle stunting to reduce the incidence of malnutrition, one of them with the provision of food combinations. Method: Journal search by collecting from multiple databases: Sage database, PubMed, IJHN, ProQuest, Ingenta Connect, and Google Scholar. Journal criteria used are journals from 2007 to 2017. Keywords used are diet diversification and stunting. Result: Nursing intervention in the form of food combinations, effective, efficient and safe are given to children born stunting to reduce the incidence of malnutrition in Indonesia. Discussion: The combination of food in an effort to fulfill the nutritional adequacy of children, influenced by economic status. So, it is necessary to choose a variety of foods that are cheap but nutritional quality remains met. Conclusion: Giving a combination of food to children born stunting can reduce the incidence of malnutrition in Indonesia.